Viral Population Heterogeneity and Fluctuating Mutational Pattern during a Persistent SARS-CoV-2 Infection in an Immunocompromised Patient - Brandolini, Martina; Zannoli, Silvia; Gatti, Giulia; Arfilli, Valentina; Cricca, Monica; Dirani, Giorgio; Denicolò, Agnese; Semprini, Simona; Grumiro, Laura; Imola, Manuela; Larne, Damiano; Marino, Maria Michela; et al. (Viruses, 2023)
Literature offers plenty of cases of immunocompromised patients, who develop chronic and severe SARS-CoV-2 infections. The aim of this study is to provide further insight into SARS-CoV-2 evolutionary dynamic taking into exam a subject suffering from follicular lymphoma, who developed a persistent infection for over 7 months. Eight nasopharyngeal swabs were obtained, and were analyses by qRT-PCR for diagnostic purposes. All of them were considered eligible (Ct < 30) for NGS sequencing. Sequence analysis showed that all sequences matched the B.1.617.2 AY.122 lineage, but they differed by few mutations identifying three genetically similar subpopulations, which evolved during the course of infection, demonstrating that prolonged replication is paralleled with intra-host virus evolution. These evidences support the hypothesis that SARS-CoV-2 adaptive capacities are able to shape a heterogeneous viral population in the context of immunocompromised patients. Spill-over of viral variants with enhanced transmissibility or immune escape capacities from these subjects is plausible.